An L-moments-based hypothesis test to identify homogeneous storm transposition regions - Benjamin FitzGerald; Daniel Wright; Lei Yan; Alyssa Hendricks Dietrich; Antonia Sebastian (Journal of Hydrology, 2026)

Correction to: Towards cleaner environment: recycling microalgal co-product to reduce emissions and impacts while eliminating fishmeal in rainbow trout feed for sustainable aquaculture - Pallab K. Sarker; Ebenezer Figueroa; Anne R. Kapuscinski; Brandi McKuin; Benjamin V. Schoffstall; Devin Fitzgerald; Connor Greenwood; Kira O’Shelski; Emily Noelle Pasion; Duncan Gwynne; Diego Gonzalez Orcajo; Sofie Andrade; et al. (Environmental Science and Pollution Research, 2026)

Cellular and Extracellular MicroRNA Dysregulation in LRRK2-Linked Parkinson’s Disease - Felix Knab; Jun-Hoe Lee; Raja Nirujogi; Kevin Menden; Luca Braunger; Lambrianna Logarnudi; Benjamin Riebenbauer; Fatma Busra Isik; Anto Praveen Rajkumar; Stefan Czemmel; Julia Fitzgerald; Thomas Gasser; et al. (Molecular Neurobiology, 2026)
Cell-free microRNAs in body fluids have emerged as promising biomarker candidates in neurodegenerative diseases. While several studies have identified dysregulated miRNAs in sporadic Parkinson’s disease, it remains unclear whether distinguishable alterations of cell-free miRNAs occur in genetic forms of the disease, such as those associated with the LRRK2 G2019S mutation. In this proof-of-concept study, we used a human induced pluripotent stem cell-derived dopaminergic neuron model to investigate whether the LRRK2 G2019S mutation induces detectable changes in the intra- and extracellular miRNAome, and whether miRNA signatures identified in vitro can be validated in patient-derived cerebrospinal fluid. We differentiated dopaminergic neurons from induced pluripotent stem cells carrying the LRRK2 G2019S mutation and an isogenic gene-corrected control. Extracellular vesicles were isolated from the culture medium and used as a source of cell-free miRNA. Next, small RNA libraries were generated and analyzed. Differentially expressed microRNAs were validated in an independent batch using RT-qPCR. We further quantified candidate microRNAs in cerebrospinal fluid samples from five LRRK2 G2019S patients and matching healthy controls. The patient cohort included the fibroblast donor from whom the stem cells were originally derived. We successfully isolated extracellular vesicles from induced pluripotent stem cell-derived human dopaminergic neurons. We identified a distinct set of differentially expressed miRNAs in cellular and cell-free RNA, among which let-7g-5p and miR-21-5p were consistently upregulated and validated across independent replicates. These alterations were reflected in the cerebrospinal fluid of the original donor and partially reproduced in additional LRRK2 patients, supporting the concept of patient-specific signatures. A strong correlation between intra- and extracellular miRNA expression was observed. Our findings demonstrate that induced pluripotent stem cell-derived dopaminergic neurons can serve as a model to identify individualized, cell-free microRNA signatures associated with the LRRK2 G2019S mutation. The dysregulated miRNAs detected in vitro were mirrored in patient cerebrospinal fluid, supporting their potential as accessible molecular readouts. These results lay the groundwork for personalized biomarker strategies in genetic forms of Parkinson’s disease and warrant further validation in larger patient cohorts.

Investigating the Benefits of Integrating Rainbow Trout (Oncorhynchus mykiss) and Lettuce (Lactuca sativa) Cultivation in California - Duncan Gwynne; Pallab K. Sarker; Anne R. Kapuscinski; Benjamin V. Schoffstall; Devin Fitzgerald; Megan Deevy; Joji Muramoto; Uchasha Sarker; Stavros Boutris; Catalina Sutter; Emily Thompson; Lucas Raymond (Fishes, 2025)
Global food production, both aquatic and terrestrial, is rife with sustainability issues. Aquaculture is a rapidly growing industry that is on track to surpass wild-caught fishery production by 2030. The integration of aquaculture and agriculture systems could help to reduce some of their respective and shared environmental issues. Integrated Aquaculture–Agriculture (IAA) has been shown to provide a variety of benefits to both aquaculture and agriculture including increased system water use efficiency (WUE), a reduction in fertilizer use, and increases in total farm yield and resilience. This study was performed to examine the potential for rainbow trout aquaculture effluent to improve the yield, nutrient composition, and WUE of lettuce, as well as act as a partial fertilizer replacement. We used four irrigation treatments throughout the experiment: city water, aquaculture effluent, city water with added organic fertilizer, and aquaculture effluent with added organic fertilizer. Throughout the trial, there were some issues of herbivory in the growing plot, but overall, the lettuce receiving city water with organic fertilizer (30. ± 3.4 g/plant) showed significantly higher fresh biomass than effluent treatments (18 ± 1.4 g/plant and 17 ± 2.9 g/plant) at the end of the trial. We did not detect any significant differences among treatments in the macro- and micronutrients of the lettuce shoots and roots. However, the WUE of effluent treatments (4.4 ± 0.030 kg/m3 and 1.0 ± 0.070 kg/m3) was greater than that of organic fertilizer (0.28 ± 0.050 kg/m3) and control treatments (0.23 ± 0.040 kg/m3). The results indicate that adopting IAA in California could improve statewide WUE and conserve water for sustainable agricultural production.

Towards cleaner environment: recycling microalgal co-product to reduce emissions and impacts while eliminating fishmeal in rainbow trout feed for sustainable aquaculture - Pallab K. Sarker; Ebenezer Figueroa; Anne R. Kapuscinski; Brandi McKuin; Benjamin V. Schoffstall; Devin Fitzgerald; Connor Greenwood; Kira O’Shelski; Emily Noelle Pasion; Duncan Gwynne; Diego Gonzalez Orcajo; Sofie Andrade; et al. (Environmental Science and Pollution Research, 2024)
The rapid increase in aquaculture over the last several decades has led to concerns about the environmental impact of fish feeds relying on marine resources for fishmeal (FM). We aim to assess Nannochloropsis sp. QH25 co-product as a viable and sustainable replacement for FM in juvenile rainbow trout, Oncorhynchus mykiss , feeds. We formulated four experimental diets: a reference (FM based), 33N, 66N, and 100N diet (33%, 66%, and 100% co-product replacement). Rainbow trout were randomly assigned to one of 16 tanks and randomly assigned an experimental diet to consume throughout the experiment (64 days total), with four replicate tanks per diet. We compared the phosphorus (P) and nitrogen (N) digestibility, emissions, and growth between diets and, compared six environmental impacts (biotic resource use (BRU), global warming potential (GWP), water use, land use, marine eutrophication potential (MEP), and freshwater eutrophication potential (FEP)) of each diet. Our results indicate that replacing FM with co-product did not significantly alter growth. P digestibility of the experimental and reference diets was comparable. BRU conversion ratio was significantly lower in the experimental diets. However, there were significantly higher water and land use conversion ratios but insignificantly higher results in GWP, MEP, and FEP between the reference and 100N diet.

Extrusion processing improves rainbow trout digestibility of microalgal Nannochloropsis oculata co-product biomass for more sustainable aquaculture diets - Pallab K. Sarker; Anne R. Kapuscinski; Devin Fitzgerald; Connor Greenwood; Pablo Nocera; Kira O'Shelski; Benjamin Lee; Abel Mkulama; Sofie Andrade; Duncan Gwynne; Diego Gonzalez Orcajo; Lydia Warkaw; et al. (Algal Research, 2023)

Comparison of willingness and preference for genetic counseling via telemedicine: before vs. during the COVID-19 pandemic - Camille O. Allison; Sandra K. Prucka; Sara M. Fitzgerald-Butt; Benjamin M. Helm; Melissa Lah; Leah Wetherill; Rebecca E. Baud (Journal of Community Genetics, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantifying thermal exposure for migratory riverine species: Phenology of Chinook salmon populations predicts thermal stress - Alyssa M. FitzGerald; Sara N. John; Travis M. Apgar; Nathan J. Mantua; Benjamin T. Martin (Global Change Biology, 2021)
Migratory species are particularly vulnerable to climate change because habitat throughout their entire migration cycle must be suitable for the species to persist. For migratory species in rivers, predicting climate change impacts is especially difficult because there is a lack of spatially continuous and seasonally varying stream temperature data, habitat conditions can vary for an individual throughout its life cycle, and vulnerability can vary by life stage and season. To predict thermal impacts on migratory riverine populations, we first expanded a spatial stream network model to predict mean monthly temperature for 465,775 river km in the western U.S., and then applied simple yet plausible future stream temperature change scenarios. We then joined stream temperature predictions to 44,396 spatial observations and life‐stage‐specific phenology (timing) for 26 ecotypes (i.e., geographically distinct population groups expressing one of the four distinct seasonal migration patterns) of Chinook salmon ( Oncorhynchus tshawytscha ), a phenotypically diverse anadromous salmonid that is ecologically and economically important but declining throughout its range. Thermal stress, assessed for each life stage and ecotype based on federal criteria, was influenced by migration timing rather than latitude, elevation, or migration distance such that sympatric ecotypes often showed differential thermal exposure. Early‐migration phenotypes were especially vulnerable due to prolonged residency in inland streams during the summer. We evaluated the thermal suitability of 31,699 stream km which are currently blocked by dams to explore reintroduction above dams as an option to mitigate the negative effects of our warmer stream temperature scenarios. Our results showed that negative impacts of stream temperature warming can be offset for almost all ecotypes if formerly occupied habitat above dams is made available. Our approach of combining spatial distribution and phenology data with spatially explicit and temporally explicit temperature predictions enables researchers to examine thermal exposure of migrating populations that use seasonally varying habitats.

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Multimodel ensembles improve predictions of crop–environment–management interactions - Daniel Wallach; Pierre Martre; Bing Liu; Senthold Asseng; Frank Ewert; Peter J. Thorburn; Martin van Ittersum; Pramod K. Aggarwal; Mukhtar Ahmed; Bruno Basso; Christian Biernath; Davide Cammarano; et al. (Global Change Biology, 2018)
A recent innovation in assessment of climate change impact on agricultural production has been to use crop multimodel ensembles ( MME s). These studies usually find large variability between individual models but that the ensemble mean (e‐mean) and median (e‐median) often seem to predict quite well. However, few studies have specifically been concerned with the predictive quality of those ensemble predictors. We ask what is the predictive quality of e‐mean and e‐median, and how does that depend on the ensemble characteristics. Our empirical results are based on five MME studies applied to wheat, using different data sets but the same 25 crop models. We show that the ensemble predictors have quite high skill and are better than most and sometimes all individual models for most groups of environments and most response variables. Mean squared error of e‐mean decreases monotonically with the size of the ensemble if models are added at random, but has a minimum at usually 2–6 models if best‐fit models are added first. Our theoretical results describe the ensemble using four parameters: average bias, model effect variance, environment effect variance, and interaction variance. We show analytically that mean squared error of prediction ( MSEP ) of e‐mean will always be smaller than MSEP averaged over models and will be less than MSEP of the best model if squared bias is less than the interaction variance. If models are added to the ensemble at random, MSEP of e‐mean will decrease as the inverse of ensemble size, with a minimum equal to squared bias plus interaction variance. This minimum value is not necessarily small, and so it is important to evaluate the predictive quality of e‐mean for each target population of environments. These results provide new information on the advantages of ensemble predictors, but also show their limitations.

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Priority Actions for Sustainable Forest Management in the International Year of Forests - DOMINICK A. DELLASALA; JOHN M. FITZGERALD; BENGT‐GUNNAR JONSSON; JEFFREY A. MCNEELY; BENJAMIN DELALI DOVIE; MARTIN DIETERICH; PATRICIA MAJLUF; SIMON C. NEMTZOV; OWEN T. NEVIN; E. CHRISTIEN M. PARSONS; JAMES E.M. WATSON (Conservation Biology, 2012)